Privative Clauses: Post-Fire Bricks Development And Trend - Gan, Ching Chuan (Journal of Malaysian and Comparative Law, 1991)
This article will attempt to highlight the recent development in case law relating to privative clauses in this country and the legislative trend relating thereto. It will be beyond the scope of this article to analyse the judicial interpretation of such clauses before the landmark case of South East Asia Fire Bricks Sdn Bhd v Non-Metallic Mineral Products Manufactures Employees Union (hereinafter referred to as "the Fire Bricks case").